Why Do the Maximum Intensities in Modeled Tropical Cyclones Vary Under the Same Environmental Conditions?. Issue 3 (3rd February 2020) - Tao, Dandan; Bell, Michael; Rotunno, Richard; van Leeuwen, Peter Jan
Abstract: In this study w e explored why the different initial tropical cyclone structures can result in different steady‐state maximum intensities in model simulations with the same environmental conditions. We discovered a linear relationsh ip between the radius of maximum wind ( r m ) and the absolute angular momentum that passes through r m ( M m ) in the model simulated steady‐state tropical cyclones that r m = aM m + b . This nonnegligible intercept b is found to be the key to making a steady‐state storm with a larger M m more intense. The sensitivity experiments show that this nonzero b results mainly from horizontal turbulent mixing and decreases with decreased horizontal mixing. Using this linear relationship from the simulations, it is also found that the degree of supergradient wind is a function of M m as well as the turbulent mixing length such that both a larger M m and/or a reduced turbulent mixing length result in larger supergradient winds. Plain Language Summary: According to the maximum potential intensity theory, the maximum intensities for tropical cyclones should be the same given the same environmental conditions, which means the radius of maximum wind ( r m ) at the boundary layer top should be linearly proportional to the absolute angular momentum such that r m aM m . In model simulations, however, different initial vortex structures usually result in different quasi‐steady‐state maximum intensities. In this paper, an axisymmetric numerical model is used to evaluate the TC's maximum intensities at the quasi‐steady state and explore the cause of this discrepancy between the model simulations and the maximum potential intensity theory. The model results exhibit that the various values of r m do have a linear relation with M m, which is predicted by the maximum potential intensity theory. However, there is a non‐negligible intercept term, b, in this linear relation ( r m = aM m + b ), which is found to be the key to making a steady‐state storm with a larger M m more intense. Key Points: The steady‐state radius of maximum wind r m has a linear relationship to the absolute angular momentum M m that r m = aM m + b The nonnegligible intercept b is responsible for the various steady‐state maximum intensities Horizontal turbulent mixing acts a role on the steady‐state maximum intensities through adjusting the linear relationship between r m and M m